A verified genomic reference sample for assessing performance of cancer panels detecting small variants of low allele frequency - Jones, Wendell; Gong, Binsheng; Novoradovskaya, Natalia; Li, Dan; Kusko, Rebecca; Richmond, Todd A; Johann, Donald J; Bisgin, Halil; Sahraeian, Sayed Mohammad Ebrahim; Bushel, Pierre R; Pirooznia, Mehdi; Wilkins, Katherine; et al. (Genome biology, 2021)
BACKGROUND: Oncopanel genomic testing, which identifies important somatic variants, is increasingly common in medical practice and especially in clinical trials. Currently, there is a paucity of reliable genomic reference samples having a suitably large number of pre-identified variants for properly assessing oncopanel assay analytical quality and performance. The FDA-led Sequencing and Quality Control Phase 2 (SEQC2) consortium analyze ten diverse cancer cell lines individually and their pool, termed Sample A, to develop a reference sample with suitably large numbers of coding positions with known (variant) positives and negatives for properly evaluating oncopanel analytical performance. RESULTS: In reference Sample A, we identify more than 40,000 variants down to 1% allele frequency with more than 25,000 variants having less than 20% allele frequency with 1653 variants in COSMIC-related genes. This is 5-100× more than existing commercially available samples. We also identify an unprecedented number of negative positions in coding regions, allowing statistical rigor in assessing limit-of-detection, sensitivity, and precision. Over 300 loci are randomly selected and independently verified via droplet digital PCR with 100% concordance. Agilent normal reference Sample B can be admixed with Sample A to create new samples with a similar number of known variants at much lower allele frequency than what exists in Sample A natively, including known variants having allele frequency of 0.02%, a range suitable for assessing liquid biopsy panels. CONCLUSION: These new reference samples and their admixtures provide superior capability for performing oncopanel quality control, analytical accuracy, and validation for small to large oncopanels and liquid biopsy assays.
Keywords: alely; Humans; průběh práce; Biomarkers, Tumor; genetická heterogenita; genomika; frekvence genu; Alleles; DNA Copy Number Variations; lidé; Workflow; genetická variace; nádorové biomarkery; Genetic Variation; Genetic Heterogeneity; Neoplasms; nádorové buněčné linie; nádory; variabilita počtu kopií segmentů DNA; Gene Frequency; genetické testování; Cell Line, Tumor; Genetic Testing; Genomics